2017
DOI: 10.1186/s13229-017-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of early head circumference enlargements in children later diagnosed with autism in Israel

Abstract: BackgroundLarge controversy exists regarding the potential existence and clinical significance of larger brain volumes in toddlers who later develop autism. Assessing this relationship is important for determining the clinical utility of early head circumference (HC) measures and for assessing the validity of the early overgrowth hypothesis of autism, which suggests that early accelerated brain development may be a hallmark of the disorder.MethodsWe performed a retrospective comparison of HC, height, and weigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Some studies found increased weight in infants with ASD from as early as 1–3 months [Fukumoto et al, ; Mraz et al, ; van Daalen et al, ], other studies have reported no differences in weight until 4‐ [Torrey et al, ], 6‐ [Surén et al, ], or 11 months of age [Chawarska et al, ], or not at all [Mraz et al, ], when compared to TD infants. Similar to Dinstein et al [] the current study found that infants with ASD were lighter in weight at birth compared to TD infants; however, contrary to the earlier finding of Dissanayake et al [], infants and toddlers with ASD in our study did not display an increased acceleration in weight from birth through 3 years of age relative to the TD infants.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Some studies found increased weight in infants with ASD from as early as 1–3 months [Fukumoto et al, ; Mraz et al, ; van Daalen et al, ], other studies have reported no differences in weight until 4‐ [Torrey et al, ], 6‐ [Surén et al, ], or 11 months of age [Chawarska et al, ], or not at all [Mraz et al, ], when compared to TD infants. Similar to Dinstein et al [] the current study found that infants with ASD were lighter in weight at birth compared to TD infants; however, contrary to the earlier finding of Dissanayake et al [], infants and toddlers with ASD in our study did not display an increased acceleration in weight from birth through 3 years of age relative to the TD infants.…”
Section: Discussionsupporting
confidence: 56%
“…While studies have reported findings of “accelerated” growth in ASD, this term has been used to reflect a trend to increase in physical measures in individual age groups and is almost always used in reference to head and brain measures, rather than height and weight. In addition to Dissanayake et al [] and Dinstein et al [], the current study is the only other study to date to examine the rate of growth across all three physical parameters of HC, height, and weight from birth to three years of age; it is also the only study to examine these growth parameters in a large representative group of participants with ASD during these early years.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations